Intentionality and Players of Effective Online Courses in Mathematics - Raza, Salman Hussain; Reddy, Emmenual (Frontiers in Applied Mathematics and Statistics, 2021)
Mathematics is the engine, vehicle, driver and language of today’s initiatives, innovations and human endeavours. In this mathematical-driven world, the ability to perform mathematical tasks and logical reasoning are also essential in solving quotidian tasks and problems. Therefore, mathematical competency and problem-solving skills are kept as an integral component in almost every educational curriculum around the globe. However, there are numerous stumbling blocks along the way to successful teaching, conducive learning environment and good student performances in almost all disciplines, but more prevalent and visible in mathematics. The major concerns of educators responsible for teaching mathematics and mathematics-related courses are to find effective and innovate ways to deliver mathematical content, to extend the concepts and theories beyond the classrooms, to integrate mathematics with important concepts such as gamification, data mining, learning analytics, deep learning, and effective tools such as mobile devices, learning management systems and digital technology, and to maintain a good record of students’ performance. In online deliveries, these concerns are further escalated due to no or limited one-to-one interactions and lack of face time, to mention a few. This paper investigates the efficacy and effectiveness of traditional and innovative pedagogical practices used in online mathematic courses at the University of the South Pacific (USP). It examines the interdependence of embedded activities and students’ achievement. The results indicate that these online mathematics courses were highly dominated by conventional approaches and were less interactive and engaging; therefore, resulted in lower success rates when compared to the courses from other disciplines. To recommend possible ways to enhance the quality of learning and teaching in the online mathematics courses, selected online courses from the information system discipline were explored. The reasons for the high online presence in the course were investigated and activities that could lead to collaborative and active learning beyond the passive materials were data mined. The evidence drawn from the statistical analysis highlights the importance of including selected interactive and engaging activities in online learning space of mathematics courses to promote student engagement and help create a sense of community among geographically dispersed students.